1997
DOI: 10.1016/s0014-5793(97)00971-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of PAMP‐12 (PAMP[9–20]) in porcine adrenal medulla as a major endogenous biologically active peptide

Abstract: Proadrenomedullin N-terminal 20 peptide (PAMP-20) is a potent hypotensive peptide processed from the adrenomedullin (AM) precursor. We developed a specific radioimmunoassay which recognizes the C-terminal region of PAMP-20. Using this radioimmunoassay, the distribution of immunoreactive (ir-) PAMP was determined in porcine tissues. High concentrations of ir-PAMP were observed in the adrenal medulla and in the atrium, and these values were comparable to the corresponding concentrations of ir-AM. The concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
2
27
0
2
Order By: Relevance
“…This observation makes PAMP (12)(13)(14)(15)(16)(17)(18)(19)(20) a good candidate as a PAMP receptorselective antagonist, a contention supported by the present finding that PAMP (12)(13)(14)(15)(16)(17)(18)(19)(20), although ineffective per se, partially suppressed the PAMP inhibitory action on the secretory response of ZG and AM to Ca 2ϩ -dependent agonists. Because the PAMP(9 -20) fragment is the major endogenous PAMP peptide in porcine AM, 25 we hypothesized that posttranslational processing of the prepro-ADM molecule gives rise not only to PAMP but also its fragments. Along with our present findings concerning PAMP (12)(13)(14)(15)(16)(17)(18)(19)(20), this raises the interesting possibility that adrenal PAMP receptors may be agonistically and antagonistically modulated by endogenous ligands.…”
Section: Discussionmentioning
confidence: 99%
“…This observation makes PAMP (12)(13)(14)(15)(16)(17)(18)(19)(20) a good candidate as a PAMP receptorselective antagonist, a contention supported by the present finding that PAMP (12)(13)(14)(15)(16)(17)(18)(19)(20), although ineffective per se, partially suppressed the PAMP inhibitory action on the secretory response of ZG and AM to Ca 2ϩ -dependent agonists. Because the PAMP(9 -20) fragment is the major endogenous PAMP peptide in porcine AM, 25 we hypothesized that posttranslational processing of the prepro-ADM molecule gives rise not only to PAMP but also its fragments. Along with our present findings concerning PAMP (12)(13)(14)(15)(16)(17)(18)(19)(20), this raises the interesting possibility that adrenal PAMP receptors may be agonistically and antagonistically modulated by endogenous ligands.…”
Section: Discussionmentioning
confidence: 99%
“…This finding led us to seek novel PAMP20-related peptides in the adrenal medulla. By using an antibody recognizing the C-terminal structure of PAMP20, it was found that a high level of PAMP12, a 12 amino acid peptide identical to PAMP20 at amino acids 9-20, was present in pigs and cows (24,25). In addition, a considerable level of PAMP16, a peptide identical to PAMP20 at amino acids 5-20, was identified in the bovine adrenal medulla (24).…”
Section: Expression and Release Of Am And Pamp20 From Adrenal Chromafmentioning
confidence: 99%
“…10,22 Recently, PAMP- [9][10][11][12][13][14][15][16][17][18][19][20] (a carboxy-terminal fragment of PAMP) has been identified in porcine adrenal medulla and causes hypotension on intravenous injection in the rat. 7 Synthetic human PAMP- [12][13][14][15][16][17][18][19][20] is also a vasodepressor in the rat and cat. 8 In bovine chromaffin cells, PAMP- [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] has been reported to inhibit nicotinic agonist-induced catecholamine secretion 23 and synthesis 24 and nicotinic agonist-induced Na ϩ and Ca 2ϩ influx.…”
mentioning
confidence: 99%
“…7 Synthetic human PAMP- [12][13][14][15][16][17][18][19][20] is also a vasodepressor in the rat and cat. 8 In bovine chromaffin cells, PAMP- [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] has been reported to inhibit nicotinic agonist-induced catecholamine secretion 23 and synthesis 24 and nicotinic agonist-induced Na ϩ and Ca 2ϩ influx. 23,25 However, the precise mechanism or site of PAMP- [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]…”
mentioning
confidence: 99%
See 1 more Smart Citation